In vitro characterization of novel hyaluronan-antioxidant conjugates as potential topical therapeutics against hearing loss - Arrigali, Elizabeth M.; Veit, Joachim G. S.; Birru, Bhaskar; Van Tine, Jack; Sandau, Kolton C.; Barrett-Catton, Emma; Tonnerre, Zachary; Serban, Monica A. (Frontiers in Pharmacology, 2024)
Noise-induced hearing loss affects roughly 430 million people worldwide. Current treatment options often require invasive medical procedures, and to date, there are no FDA-approved drug therapies. While the causes can be diverse, noise induced hearing loss is unequivocally associated with oxidative stress and inflammation, and subsequent damage to the inner ear structures. Several studies have shown that various antioxidants such as glutathione, cysteine, and methionine can be used to mitigate oxidative damage from reactive oxygen species; however, these studies relied on invasive or systemic drug delivery methods. This study focused on the development and characterization of a novel series of antioxidant compounds that would be suitable for non or minimally invasive topical inner ear delivery and could mitigate reactive oxygen species associated cellular damage. Specifically, a series of covalent conjugates were synthesized by using hyaluronan as a drug carrier, and methionine, cysteine or glutathione as antioxidant drugs. The conjugates were tested for their ability to readily permeate though in vitro round window membrane and tympanic membrane permeation models, as well as their in vitro internalization into cochlear cells. Our data revealed an interdependence between the molecular weight of the hyaluronan carrier, and the tissue and cellular membrane permeation capacity. Subsequent screening of the adequately sized conjugates in in vitro acellular assays revealed the strongest antioxidant activity for the cysteine and glutathione conjugates. These oxidative stress protective effects were further confirmed in cellular in vitro assays. Collectively, the data herein showcase the potential value of these conjugates as therapeutics against oxidative-stressmediated cellular damage specific to noise-induced hearing loss.